The influence of perceived aggressive monetization on mobile gamers' in-app purchase behavior - Baskara, Andri Seta; Jimmy, So Yohannes; Natalia, Friska (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2025)
Popularity of mobile video games is rapidly increasing. A larger audience is drawn in by the increasingly captivating and visually appealing mobile gaming experiences thanks to technological advancements. The In-App Purchase (IAP) monetization model is the main revenue for most mobile games. Although the application can be used for free, users can choose to pay for extra features or content. This quantitative study sought to identify the determinant of users' willingness to spend money on IAP. This study used a construct known as Perceived Aggressive Monetization (PAM), besides variables of self-control and previous impulsive spending. This study's respondents totaled 264 and used a 5-point likert scale online questionnaire. Non-probability sampling was used in this study. This study employed PLS-SEM to analyze respondent data. Therefore, PAM emerged as a significant predictor of willingness to spend, in other words, players perceive that monetization employed in mobile games is aggressive. Meanwhile, self-control and previous impulsive spending did not significantly influence users’ willingness to spend. Mobile game studios must consider how players perceive aggressive monetization in the mobile games they play. To mitigate negative player perception, mobile game studios should prioritize the use of ethical monetization strategies, particularly those that discourage addiction to IAP.